Pengembangan e-lkpd berbasis socio scientific issue untuk meningkatkan kemampuan berpikir kreatif siswa SMP - Cici Lia Ayu Fatmawati; Ulin Nuha (Papanda Journal of Mathematics and Science Research, 2026)
Creative thinking is the ability to explore and develop original ideas that come from personal thoughts. However, in reality, students' creative thinking skills in science education are still low. Several factors that can influence this are low curiosity and inadequate learning media and approaches. This study aims to test the validity, practicality, and effectiveness of SSI (Socio Scientific Issue)-based E-LKPD in improving students' creative thinking skills in science learning. This study used the ADDIE research model, which consists of Analysis, Design, Development, Implementation, and Evaluation. SSI (Socio Scientific Issue)-based E-LKPD has been applied in science learning at SMP Negeri 6 Jember in class VIII C with the results that SSI (Socio Scientific Issue)-based E-LKPD can be declared highly valid with a percentage of 94,48%, highly practical with a percentage of 94,09%, and effective in improving creative thinking skills with an N-gain score of 0,74, which is categorized as high. It also received a very good response from students with a percentage of 91,17%. The results showed that SSI-based E-LKPD has a high level of validity, is practical for teachers and students to use, and is effective in improving creative thinking skills. This research contributes to science learning by providing contextual SSI-based E-LKPD related to scientific social issues so that it can help students connect scientific concepts with real-world problems. SSI-based E-LKPD not only supports material understanding but also stimulates curiosity and enhances creative thinking skills. Additionally, it can serve as teaching material for teachers to implement meaningful, contextual learning oriented towards 21st century skills